About My War-Time Childhood - Ilya Lezhava (Проект Байкал, 2019)
A book wouldn't be enough just to mention Ilya Nikolaevich Lezhava's creative works and achievements. We’ll certainly write it.  Upon his graduation from MArchI he became one of NER ideologists… Lezhava is the author of dozens of books and articles in famous magazines, including the iconic French magazine L'Architecture D'Aujourd'hui. PROJECT BAIKAL is proud to be among them: except Sibstream, Ilya Georgievich has published several articles about classics of the XX century (PB 46 quarters; PB 49 nature in the city; PB 53 cui prodest). His story about his war-time childhood submitted to PB contains everything that can be expected from high literature: liveliness, frank intonation, emotionality and a gift of speaking.